Principal Leadership and School Performance: An Examination of Instructional Leadership and Organizational Management. Issue 4 (2nd October 2019) - Sebastian, James; Allensworth, Elaine; Wiedermann, Wolfgang; Hochbein, Craig; Cunningham, Matthew
ABSTRACT: Recent research work in school leadership highlighting the importance of principals' organizational management skills has prompted scholars to consider their importance in relation to instructional leadership skills. However, there is limited empirical work that directly compares these leadership skills and their importance for school outcomes. In this study, we use principals' self-ratings to construct typologies of effectiveness in both domains and compare their relationship to student achievement. Our results show that principals view themselves as either strong or weak on instructional leadership and organizational management skills simultaneously. We also find that learning gains vary significantly across the principal profiles.